Effectiveness of vitamin C on biofilm formation by clinical isolates of Pseudomonas aeruginosa - Cynthia, Syeda Sadia Akther; Tasnim, Homaira (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.